Implementasi Manajemen Berbasis Sekolah (MBS) Berbasis Transformational Leadership Dalam Meningkatkan Mutu Luaran di SMAIT Insantama Bogor - M. Fuad Abdullah (Hadara : Journal of Da'wah and Islamic Civilization, 2026)
The quality of education is a strategic issue that requires systematic and innovative school management. This study aims to examine the implementation of School-Based Management (SBM) integrated with transformational leadership in improving the quality of educational outcomes at SMAIT Insantama in Bogor City. A descriptive qualitative approach was used, with data collected through in-depth interviews, observations, and document analysis. The results reveal that SMAIT Insantama implements SBM through four flagship programs: policies based on Islamic values, a curriculum in science and applied sciences, managerial and organizational training, and continuous transformative learning. Quality control is formulated in the 6i Strategic Policy as an institutional prerequisite. Tiered leadership development programs range from LDK 1, LDK 2, LKMM, CEO SMENTION, LKMA, to the Graduation Boarding School. This study shows that graduates possess interpersonal skills, analytical abilities, problem-solving skills, and a competitive global leadership spirit. The novelty of this study lies in the integration of Islamic values as the operational foundation of MBS, a model that has not been extensively examined in the national educational management literature. Implicitly, these findings recommend that national education policy adopt a character-based transformational leadership approach as a tool for improving the quality of secondary schools, particularly in the context of integrated Islamic schools.